1994
DOI: 10.1093/nar/22.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the DNA binding domain A of chromosomal protein HMG1

Abstract: We have mutated several residues of the first of the two HMG-boxes of mammalian HMG1. Some mutants cannot be produced in Escherichia coli, suggesting that the peptide fold is grossly disrupted. A few others can be produced efficiently and have normal DNA binding affinity and specificity; however, they are more sensitive towards heating and chaotropic agents than the wild type polypeptide. Significantly, the mutation of the single most conserved residue in the rather diverged HMG-box family falls in this 'in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 21 publications
3
44
0
Order By: Relevance
“…1, marked with stars) as in HMG1 domain B, suggesting that the Sin1p-(224 -304) peptide might have a rigid structure as well. It was shown that a W45R mutation in HMG1 A domain reduced the ability of this domain to bind 4WJDNA because of disruption of an ␣-helix (34,35). We, therefore, first asked how an analogous mutation in GST-Sin1p-(224 -304), W267R, might affect its binding to 4WJDNA.…”
Section: Sin1p/spt2p Domains Bind 4wjdnamentioning
confidence: 99%
See 1 more Smart Citation
“…1, marked with stars) as in HMG1 domain B, suggesting that the Sin1p-(224 -304) peptide might have a rigid structure as well. It was shown that a W45R mutation in HMG1 A domain reduced the ability of this domain to bind 4WJDNA because of disruption of an ␣-helix (34,35). We, therefore, first asked how an analogous mutation in GST-Sin1p-(224 -304), W267R, might affect its binding to 4WJDNA.…”
Section: Sin1p/spt2p Domains Bind 4wjdnamentioning
confidence: 99%
“…Mammalian HMG1 box A contains the sequence KKPRGKM. A single point mutation replacing the arginine with glycine reduces the affinity of this protein for 4WJDNA at least 10-fold (34).…”
Section: Sin1p/spt2p Domains Bind 4wjdnamentioning
confidence: 99%
“…HMG1 and -2 are ubiquitous, abundantly expressed nuclear proteins that bind nonspecifically in the minor groove of DNA via their two HMG box domains. They bind preferentially to distorted DNA, including cruciform four-way junction DNA structures (4,13,30,40), and play a role in the repair of 1,2-cis-platinum DNA intrastrand adducts (39). HMG1 and -2 also bind to and preserve negatively supercoiled DNA structures (48).…”
mentioning
confidence: 99%
“…Complexes of the [R6A]cHMGla with DNA exhibited reduced stability, as judged from the smearing of the shifted bands in the binding assay. A similar mutation in this region of ArglO of the HMGl-BD of the rat HMGl protein led to an approximately tenfold reduction of the binding affinity to four-way-junction DNA [28].…”
Section: Discussionmentioning
confidence: 94%
“…Unexpectedly, only moderate alterations of the DNAbinding and DNA-bending properties were observed in this mutant protein. Two previous mutational analyzes of the HMGlBDs of the rat HMGl protein have revealed that substitution of Trp42 in the central hydrophobic core similarly changed the conformational stability [28] and the structure [29] of the protein whereas the binding of the mutant protein to DNA was only slightly affected. The deletion of the first seven amino acid residues reduced the strength of the interaction of the cHMGla protein with DNA.…”
Section: Discussionmentioning
confidence: 94%